Tendon-Holding Capacities of Two Newly Designed Implants for Tendon Repair: An Experimental Study on the Flexor Digitorum Profundus Tendon of Sheep - EROL, BÜLENT (My University, 2014)
BACKGROUND: Two main factors determine the strength of tendon repair; the tensile strength of material and the gripping capacity of a suture configuration. Different repair techniques and suture materials were developed to increase the strength of repairs but none of techniques and suture materials seem to provide enough tensile strength with safety margins for early active mobilization. In order to overcome this problem tendon suturing implants are being developed. We designed two different suturing implants. The aim of this study was to measure tendon-holding capacities of these implants biomechanically and to compare them with frequently used suture techniques. MATERIALS AND METHODS: In this study we used 64 sheep flexor digitorum profundus tendons. Four study groups were formed and each group had 16 tendons. We applied model 1 and model 2 implant to the first 2 groups and Bunnell and locking-loop techniques to the 3rd and 4th groups respectively by using 5 Ticron sutures. RESULTS: In 13 tendons in group 1 and 15 tendons in group 2 and in all tendons in group 3 and 4, implants and sutures pulled out of the tendon in longitudinal axis at the point of maximum load. The mean tensile strengths were the largest in group 1 and smallest in group 3. CONCLUSION: In conclusion, the new stainless steel tendon suturing implants applied from outside the tendons using steel wires enable a biomechanically stronger repair with less tendon trauma when compared to previously developed tendon repair implants and the traditional suturing techniques.
Keywords: Early mobilization; implant; tendon repair; tendon ruptures.